PTH-049 Successful Reversal of High Titre Antibodies to Infliximab and Adalimumab with The Addition of Immunomodulator Therapy. (17th August 2016) - Bond, A; Clark, K; Gregg, B; Collins, P; Dibb, M; Probert, C; Subramanian, S
Abstract : Introduction: Immunogenicity is a common problem associated with anti-tumour necrosis factor (TNF) therapy and is often associated with loss of clinical response. Concomitant immunomodulatory therapy reduces the rate of anti-drug antibody (ADA) formation with infliximab and is associated with better outcomes. 1 However, the impact of immunomodulator initiation specifically to reverse established ADA has not been adequately investigated. Current guidelines recommend switching of anti-TNF agent or class switch in the presence of ADA titre >9 u/ml. However, outcomes with further biologics are poor and reversal of ADA may be preferable. We report the successful reversal of very high titre ADA with immunomodulator initiation. Methods: This was a retrospective study of patients with established ADA on infliximab or adalimumab monotherapy, in whom an immunomodulator was commenced. Levels of ADA and trough levels of drug were monitored by ELISA (Theradiag). Results: Four patients were included (3 Crohn's disease and 1 ulcerative colitis), of which two patients were receiving infliximab and 2 adalimumab. There were 3 males and 1 female with a mean age of 50 years (SD ±17.6). All patients had initial titres of ADA > 200 ng/ml for infliximab and >160 ng/ml for adalimumab, with undetectable trough levels (<0.1 µg/ml). Three patients were treated with thiopurines and one with methotrexate. Three patients (2 thiopurines, 1 methotrexate) had successful reversal of antibodies accompanied by an increase in trough levels and clinical improvement. One infliximab and one adalimumab patient also had dose escalation after reversal of ADA to achieve therapeutic drug concentration. One patient who achieved reversal stopped their thiopurine due to side effects and had recurrence of ADA and a subsequent loss of response. Conclusion: In patients undergoing monotherapy with anti-TNF treatment who develop ADA, the addition of an immunomodulator agent has the potential to reverse even high antibody titres and regain clinical response. This strategy is particularly useful as the risk of ADA with a subsequent anti-TNF is higher in patients with ADA to one anti-TNF agent[2]. References: 1 Ruffolo C, Scarpa M, Bassi N. Infliximab, azathioprine, or combination therapy for Crohn's disease. N Engl J Med 2010;363 :1086–8. doi:10.1056/NEJMoa0904492 2 Frederiksen MT, Ainsworth MA, Brynskov J, Thomsen OO, Bendtzen K SC. Antibodies against infliximab are associated with de novo development of antibodies to adalimumab and therapeutic failure in infliximab-to-adalimumab switchers with IBD. Inflamm Bowel Dis 2014;20 :1714–21. Disclosure of Interest: None Declared